The Importance of Preoperatively Calculated Halp Score in Differentiating Complicated Acute Appendicitis in Patients With Acute Appendicitis - Ag, Onur; Kutluer, Nizamettin; Ogut, Mehmet Zeki; Azak Bozan, Ayse; Ebiloglu, Mehmet Fatih; Gunes, Burak; Bozan, Mehmet Bugra (Wiley, 2026)
Background/Aims: The HALP score, a scoring method that has demonstrated effectiveness in inflammatory clinical conditions and is increasingly used in clinical practice, can be utilized to distinguish between complicated and uncomplicated cases of acute appendicitis. Additionally, it may serve as a reference for initiating medical treatment at an earlier stage. Materials and Methods: Patients who were diagnosed with acute appendicitis and operated on were included. Patients who underwent conventional open appendectomy and laparoscopic appendectomy as surgical procedures were examined retrospectively by scanning their files. Preoperative CBC and biochemistry values of the patients were recorded by scanning their files retrospectively. From here, preoperative hemoglobin-albumin-lymphocyte-platelet (HALP) Score [hemoglobin (g/L) x albumin (g/L) x lymphocyte count (/L)]/platelet count (/L)], neutrophil-lymphocyte ratio (NLR) [neutrophil count (/L)/lymphocyte count (/L)] and platelet-lymphocyte ratio (PLR) [platelet count (/L)/lymphocyte count (/L)] were calculated manually. Results: There were statistically significant differences between patients with and without complications in terms of preoperative WBC, neutrophil counts and lymphocyte counts in the preoperative period (p values; 0.015, < 0.006 and < 0.004, respectively). There was no statistically significant difference in terms of other preoperative blood values (p > 0.05). There was a statistically significant difference between the groups in terms of NLR, PLR, and HALP score calculated from preoperative CBC parameters. Conclusion: HALP score is an important biomarker, like other biomarkers, in the early diagnosis of complications, initiating antibiotic therapy earlier, gaining time during transport, and preventing complications that may arise due to exacerbation of the disease. Trial Registration: NCT07002671
Keywords: Immature Granulocyte Count; Percentage; Hemoglobin; Lymphocyte; Diagnosis; Platelet; Albumin